Fecal sacs attract insects to the nest and provoke an activation of the immune system of nestlings. Issue 1 (December 2016) - Ibáñez-Álamo, Juan; Ruiz-Raya, Francisco; Rodríguez, Laura; Soler, Manuel
Abstract Background Nest sanitation is a widespread but rarely studied behavior in birds. The most common form of nest sanitation behavior, the removal of nestling feces, has focused the discussion about which selective pressures determine this behavior. The parasitism hypothesis, which states that nestling fecal sacs attract parasites that negatively affect breeding birds, was proposed 40 years ago and is frequently cited as a demonstrated fact. But, to our knowledge, there is no previous experimental test of this hypothesis. Results We carried out three different experiments to investigate the parasitism hypothesis. First, we used commercial McPhail traps to test for the potential attraction effect of nestling feces alone on flying insects. We found that traps with fecal sacs attracted significantly more flies (Order Diptera), but not ectoparasites, than the two control situations. Second, we used artificial blackbird (Turdus merula ) nests to investigate the combined attraction effect of feces and nest materials on arthropods (not only flying insects). Flies, again, were the only group of arthropods significantly attracted by fecal sacs. We did not detect an effect on ectoparasites. Third, we used active blackbird nests to investigate the potential effect of nestling feces in ecto- and endoparasite loads in real nestlings. The presence of fecal sacs near blackbird nestlings did not increase the number of louse flies or chewing lice, and unexpectedly reduced the number of nests infested with mites. The endoparasite prevalence was also not affected. In contrast, feces provoked an activation of the immune system as the H/L ratio of nestlings living near excrements was significantly higher than those kept under the two control treatments. Conclusions Surprisingly, our findings do not support the parasitism hypothesis, which suggests that parasites are not the main reason for fecal sac removal. In contrast, the attraction of flies to nestling feces, the elevation of the immune response of chicks, and the recently described antimicrobial function of the mucous covering of fecal sacs suggest that microorganisms could be responsible of this important form of parental care behavior (microbial hypothesis).